Exploring the neuroprotective potential of Nrf2-pathway activators against annonacin toxicity - Márcia F. D. Costa; Thomas W. Rösler; Günter U. Höglinger (Scientific Reports, 2024)
Abstract Modulation of the Nrf2 pathway, a master regulator of the antioxidant response and cellular metabolism, has been suggested as a promising therapeutic strategy in tauopathies, a heterogeneous group of neurodegenerative disorders characterized by intracellular proteinaceous inclusions of abnormally phosphorylated tau. Here, we explored the neuroprotective potential of different Nrf2-pathway activators in human immortalized dopaminergic neurons against annonacin-induced toxicity, a mitochondrial inhibitor associated with a PSP-like syndrome and capable of mimicking tauopathy-like features. Interestingly, we observed heterogenous and compound-dependent neuroprotective effects among the different Nrf2-pathway activators. With the exception of Fyn inhibitors, all the selected Nrf2-pathway activators improved cell viability and the oxidative status, and reduced the annonacin-induced tau hyperphosphorylation and neurite degeneration, particularly the p62-activators. However, improvement of the impaired mitochondrial function was only observed by the Bach-1 inhibitor. Surprisingly, we found evidence that ezetimibe, an approved drug for hypercholesterolemia, prevents the transcriptional upregulation of 4R-tau triggered by annonacin insult. Overall, our results suggest that the neuroprotective effects of the Nrf2-pathway activators against annonacin toxicity may rely on the specific mechanism of action, intrinsic to each compound, and possibly on the concomitant modulation of additional signaling pathways. Further research will be needed to fully understand how synergistic modulation of metabolic adaptation and cell survival can be exploit to develop new therapeutical strategies for tauopathies and eventually other neurodegenerative diseases.